PERAN AKTIF PEREMPUAN MUSLIM - Munir, Taufik (IAIN Pekalongan, 2014)
Abstract : Issues on the Status of Women in Islam will always be a discourse which is always inviting pros and cons. Although in terms of women's rights has been codified in revelation and tradition of the Prophet (Hadith), but it turns out after him after the death, the condition of Muslim women considered to be undergoing drastic changes. The amendment relates to the concept of women's liberation, along with changes in the interpretation of the validity of the scholars of fiqh sources-formal legal about women's rights in Islam. The emergence of stigmatization in our society, that women do not need to play outside the home also play a role worsen climate of freedom for women. Abstrak : Isu tentang Status Perempuan dalam Islam akan selalu menjadi wacana yang selalu mengundang pro dan kontra. Meskipun dalam hal hak-hak perempuan telah dikodifikasi dalam wahyu dan tradisi Nabi (Hadis), tetapi ternyata setelah dia setelah kematian, kondisi perempuan Muslim dianggap mengalami perubahan drastis. Perubahan tersebut berkaitan dengan konsep pembebasan perempuan, bersama dengan perubahan dalam interpretasi validitas ulama sumber formal hukum tentang hak-hak perempuan dalam Islam fiqh. Munculnya stigmatisasi di masyarakat kita, bahwa wanita tidak perlu bermain di luar rumah juga berperan memperburuk iklim kebebasan bagi perempuan